Protective effect of Photobiomodulation Therapy and Bone Marrow Stromal Stem Cells Conditioned Media on Pheochromocytoma Cell Line 12 Against Oxidative Stress Induced by Hydrogen Peroxide - khoshsirat, Shahrok; Abbaszadeh, Hojjat Allah; Khoramgah, Maryam Sadat; Darabi, Shahram; Ahmady Roozbahani, Navid; Ahrabi, Behnaz; bahrami, Maryam; vafaei-nezhad, saeed; Tahmasebinia, Foozhan; poorhassan, mahnaz (Journal of Lasers in Medical Sciences, 2019)
Introduction: Bone marrow stromal stem cells (BMSCs), a type of adult stem cells, secrete bioactive molecules such as trophic factors, growth factors, chemokine and cytokines that may be effective against oxidative stress in neurodegenerative diseases. In this study, we examined the protective effect of BMSCs conditioned media CM) and photobiomodulation therapy (PBMT) on PC12 cells exposed to H2O2 as an oxidative injury model. Methods: BMSCs were cultured and confirmed by flow cytometry analysis and underwent osteogenic and adipogenic differentiation. Then, PC12-H2O2 cells were co-treated with BMSCs-CM and PBMT. The effect of BMSCs-CM and PBMT (He-Ne laser, 632.8 nm, 3 mW, 1.2 J/cm2, 378 s) on Bax/Bcl2 expression, cell viability, was assessed by real-time PCR and MTT assay. The length of the Neurite and cell body areas were assessed by Cell A software. Results: Flowcytometry analysis, as well as osteogenic and adipogenic staining, confirmed the BMSCs. The length of the Neurite was the highest in the group which received CM+PBMT and cell body areas were significant in CM+PBMT compared to other groups. Based on our results, elevating H2O2 concentration increased cell death significantly and using concentrations of 250 μM resulted in a dramatic increase in the mortality compared to the other groups. Conclusion: Our result demonstrated that the combination of CM +PBMT has a protective effect on PC12 cells against oxidative stress.